Analisis Kecelakaan Kerja pada Pekerja Bengkel Las - Roza Asnel; Suci Destry Ananda; Rahmi Pramulia Fitri; Suryani; Kursiah Warti Ningsih (STIKes Payung Negeri Pekanbaru, 2023)
Work accident is a human error that often occurs in workers. Especially in the welding industry or welding workshops whose work does not escape from dangerous tools and materials. This study was conducted to determine what factors are associated with work accidents in welding workshop workers in Tuah Madani sub-district in 2022. The research design used was a cross-sectional study. The responden were 41 workers from 12 welding workshops in the Tuah Madani sub-district, Pekanbaru city. Data analysis used univariate and bivariate analysiswith chi-square test. The results showed that 39.% of respondents experienced work accidents, 66.9% of respondents experienced unsafe action, 63.4% of respondents experienced unsafe conditions, 56.1% of respondents were workers with age at risk, 43.9% of respondents had knowledge of not good. From the results of statistical tests using chi-square, it can be concluded that there is a relationship between unsafe action and work accidents, there is a relationship between unsafe conditions and work accidents, and there is a relationship between knowledge and work accidents. This study shows that age does not have a significant relationship with work accidents